Analisis Pengaruh Elemen Desain Grafis dan Atribut Kemasan terhadap Minat Beli Konsumen:Studi Kasus Kemasan Mie Instan - Raymond; Deli; Bayu Syahputra (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2025)
Graphic design on product packaging plays an important role in shaping consumer perceptions and influencing purchasing decisions, especially for daily necessities such as instant noodles. This study aims to analyze the influence of graphic design elements (color, typography, images, shapes) and packaging attributes (brand, MUI logo, label) on consumer purchasing interest. The method used is a quantitative approach with the MDLC (Multimedia Development Life Cycle) model to design the research instrument and process. Data were collected through questionnaires distributed to 110 housewives in Batam City as the main respondents. The results of the regression analysis showed that graphic design elements and packaging attributes simultaneously had a significant effect on purchasing interest (F count = 30,871; sig. = 0,000). Partially, graphic design elements (sig. = 0,001) and packaging attributes (sig. = 0,004) also showed a significant influence. These findings emphasize the importance of visual strategies in product packaging to increase consumer appeal and trust. This study recommends that manufacturers optimally integrate visual elements and information in packaging to increase purchasing interest, especially from the housewife segment.